Antimicrobial activity of α-mangostin against Staphylococcus species from companion animals in vitro and therapeutic potential of α-mangostin in skin diseases caused by S. pseudintermedius - Park, Seong Yong; Lee, Jung Hwa; Ko, Seo Yeon; Kim, Nayeong; Kim, Seong Yeop; Lee, Je Chul (Frontiers in Cellular and Infection Microbiology, 2023)
Antimicrobial resistance in Staphylococcus species from companion animals is becoming increasingly prevalent worldwide. S. pseudintermedius is a leading cause of skin infections in companion animals. α-mangostin (α-MG) exhibits various pharmacological activities, including antimicrobial activity against G (+) bacteria. This study investigated the antimicrobial activity of α-MG against clinical isolates of Staphylococcus species from companion animals and assessed the therapeutic potential of α-MG in skin diseases induced by S. pseudintermedius in a murine model. Furthermore, the action mechanisms of α-MG against S. pseudintermedius were investigated. α-MG exhibited antimicrobial activity against clinical isolates of five different Staphylococcus species from skin diseases of companion animals in vitro, but not G (-) bacteria. α-MG specifically interacted with the major histocompatibility complex II analogous protein (MAP) domain-containing protein located in the cytoplasmic membrane of S. pseudintermedius via hydroxyl groups at C-3 and C-6. Pretreatment of S. pseudintermedius with anti-MAP domain-containing protein polyclonal serum significantly reduced the antimicrobial activity of α-MG. The sub-minimum inhibitory concentration of α-MG differentially regulated 194 genes, especially metabolic pathway and virulence determinants, in S. pseudintermedius. α-MG in pluronic lecithin organogel significantly reduced the bacterial number, partially restored the epidermal barrier, and suppressed the expression of cytokine genes associated with pro-inflammatory, Th1, Th2, and Th17 in skin lesions induced by S. pseudintermedius in a murine model. Thus, α-MG is a potential therapeutic candidate for treating skin diseases caused by Staphylococcus species in companion animals.